1996
DOI: 10.1007/bf00222960
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Haynaldia villosa chromosomes added to wheat using a sequential C-banding and genomic in situ hybridization technique

Abstract: Genomic in situ hybridization (GISH) offers a convenient and effective method for cytological detection, but can not determine the identity of the chromosomes involved. We integrated C-banding with GISH to identify Haynaldia villosa chromosomes in a wheat background. All chromosomes of H. villosa showed C-bands, either in telomeric regions or in both telomeric and centromeric regions, which allowed unequivocal identification of each H. villosa chromosome. The seven pairs of H. villosa chromosomes were differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…With the introduction of alien chromatin into wheat, many useful markers such as morphological markers (Zhong and Qualset 1990), biochemical markers (Li et al 2009), and cytological markers (Zhong et al 1996) have been developed to monitor the behaviour of the alien chromosomes. However, the major limitation of these techniques is that they are highly technical and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of alien chromatin into wheat, many useful markers such as morphological markers (Zhong and Qualset 1990), biochemical markers (Li et al 2009), and cytological markers (Zhong et al 1996) have been developed to monitor the behaviour of the alien chromosomes. However, the major limitation of these techniques is that they are highly technical and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang and Gill (1993) proved that the sequential GISH after N-banding or C-banding gives satisfactory results. Zhong et al (1996) also reported that prior Cbanding has only a slight negative effect on the subsequent GISH. In this study, the sequential C-banding after multicolor fluorescence GISH analysis gave better results compared with the sequential GISH after the C-banding treatment, and enabled us not only to distinguish the H. villosa and rye chromatins from the wheat chromatin simultaneously, but also to identify the alien chromosomes and chromosomal segments.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, C-banding analysis before or after GISH is effective and useful for identifying alien chromatins (Hutchinson and Seal, 1983;Jiang and Gill, 1993;Zhong et al, 1996). In this study, we report the results of the introduction of multi-alien chromatins with different powdery mildew-resistant genes from S. cereale and H. villosa and the simultaneous identification of these chromatins in a wheat background by multicolor fluorescence GISH analysis.…”
Section: Introductionmentioning
confidence: 97%
“…However, when these two techniques are used separately, it is often difficult to identify the alien chromosomes, especially translocated chromosomes. These two techniques can also be sequentially performed on the same cytological preparations (Jiang and Gill 1993b;Zhong et al 1996;Cai et al 1998;Schubert et al 1998). One problem with sequential analysis is that the quality of subsequent banding or in situ hybridization tends to be less than optimal, owing to the previous treatments.…”
Section: Discussionmentioning
confidence: 99%